Effect of Pig-Adipose-Derived Stem Cells’ Conditioned Media on Skin Wound-Healing Characteristics In Vitro - Wiśniewska, Joanna (Int J Mol Sci, 2021)
The primary mechanism by which adipose-derived stem cells (ASCs) exert their reparative or regenerative potential relies predominantly on paracrine action. Secretory abilities of ASCs have been found to be amplified by hypoxia pre-conditioning. This study investigates the impact of hypoxia (1% O(2)) on the secretome composition of pig ASCs (pASCs) and explores the effect of pASCs’ conditioned media (CM) on skin cell functions in vitro and the expression of markers attributed to wound healing. Exposure of pASCs to hypoxia increased levels of vascular endothelial growth factor (VEGF) in CM-Hyp compared to CM collected from the cells cultured in normoxia (CM-Nor). CM-Hyp promoted the migratory ability of pig keratinocytes (pKERs) and delayed migration of pig dermal fibroblasts (pDFs). Exposure of pKERs to either CM-Nor or CM-Hyp decreased the levels of pro-fibrotic indicators WNT10A and WNT11. Furthermore, CM-Hyp enhanced the expression of KRT14, the marker of the basal epidermis layer. In contrast, CM-Nor showed a stronger effect on pDFs manifested by increases in TGFB1, COL1A1, COL3A1, and FN1 mRNA expression. The formation of three-dimensional endothelial cell networks was improved in the presence of CM-Hyp. Overall, our results demonstrate that the paracrine activity of pASCs affects skin cells, and this property might be used to modulate wound healing.